Istihsan's Contribution to Online Buying and Selling Practices and Its Influence on Economic Growth in Indonesia - Mutiara, Tira; Muhajirin, Muhajirin (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2024)
This study aims to analyze the contribution of istihsan as a source of law in online buying and selling practices and its impact on economic growth in Indonesia. This study uses secondary data collected through literature studies obtained from books, journals, and the internet which are then analyzed using qualitative descriptive methods. This study found that online buying and selling practices use the salam and istishna contracts in their implementation. In general, both contracts are invalid because the goods are intangible. However, these two contracts are still valid based on istihsan bin nash and istihsan bi al-'urf. The permissibility of online buying and selling is reinforced by the DSN-MUI Fatwa No: 146 / DSN-MUI / XXI / 2021 Concerning Online Shops Based on Sharia Principles. The contribution of online buying and selling to economic growth in Indonesia occurs through the circulation of money, the provision of goods and services, and the absorption of labor. The number of businesses in this sector grew by 4.46% in 2022 with an estimated number of businesses of 2.99 million, having diverse incomes, even reaching IDR 50 billion per business, and being able to absorb 8.08% of workers from the entire working population. Without a clear legal source, the phenomenon of economic growth, one of which is caused by online buying and selling activities, is impossible.